2019
DOI: 10.3390/e21010075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicon Content on the Microstructures and Mechanical Properties of (AlCrTiZrV)-Six-N High-Entropy Alloy Films

Abstract: A series of (AlCrTiZrV)-Six-N films with different silicon contents were deposited on monocrystalline silicon substrates by direct-current (DC) magnetron sputtering. The films were characterized by the X-ray diffractometry (XRD), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), and nano-indentation techniques. The effects of the silicon content on the microstructures and mechanical properties of the films were investigated. The experimental results show that the (Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…28 Several studies on multi-component nitride coatings have studied the variation of Si content in the materials. 56,[61][62][63] A secondary amorphous phase is indeed formed at high enough Si contents; see, e.g., Fig. 8 showing HRTEM images from Lin et al 63 However, it seems that the attained nanocomposite is more diffuse than the well-known ternary super-hard materials (e.g., nc-TiN/a-Si 3 N 4 ) and thus does not lead to the same hardening.…”
Section: Journal Of Applied Physicsmentioning
confidence: 96%
“…28 Several studies on multi-component nitride coatings have studied the variation of Si content in the materials. 56,[61][62][63] A secondary amorphous phase is indeed formed at high enough Si contents; see, e.g., Fig. 8 showing HRTEM images from Lin et al 63 However, it seems that the attained nanocomposite is more diffuse than the well-known ternary super-hard materials (e.g., nc-TiN/a-Si 3 N 4 ) and thus does not lead to the same hardening.…”
Section: Journal Of Applied Physicsmentioning
confidence: 96%
“…It showed that the phase structure changes from the amorphous to the face-centered cubie (FCC) structure with increasing N content, which was proved to be related with the atomic size difference in the alloy system. Similarly, (AlCrTiZrV)Si x N high entropy film was prepared and characterized by Niu et al [ 36 ]. Then, an Al 0.5 CoCrCuFeNi coating was successfully prepared on an AZ91D magnesium alloy surface [ 37 ], and an AlCoCrFeNi coating was prepared on the stainless steel substrate [ 38 ].…”
Section: Mechanical Behaviorsmentioning
confidence: 99%
“…In this work, high-entropy nitrides (HENs) were investigated, which have been studied hitherto mainly for their application possibilities as hard coatings due to their promising mechanical properties. [1][2][3][4][5][6][7][8][9][10] HENs tend to crystallize in an ordered face centered cubic NaCl structure with nitrogen amount of %50 at.-%. [11] In contrast, high-entropy alloys and oxides (HEA, HEO), as well as transition metal nitrides have drawn some interest in applications as noble metal free catalysts, for example, for (solar) water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, high‐entropy nitrides (HENs) were investigated, which have been studied hitherto mainly for their application possibilities as hard coatings due to their promising mechanical properties. [ 1–10 ] HENs tend to crystallize in an ordered face centered cubic NaCl structure with nitrogen amount of ≈50 at.‐%. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%